(untitled) (Forum Penelitian Agro Ekonomi, 2023)
A food crisis is a disaster that prevents humans from fulfilling their basic needs. On the other side, the increasing position gap between women and men confirms that women are more food insecure than men. This paper discusses the results of a review of some literature and secondary data related to the resilience of women farmers, especially those who are headed households, and their characteristics when facing food crises. The results of this review show that women farmers who are headed households are in the position of informal workers with domestic burdens, the responsibility to meet the family’s food needs while producing food. Thus, resilience is carried out by women farmers who have the status of head of household by enabling themselves to improve family welfare. In order to achieve family welfare, land ownership is key in fulfilling household food security. The review results provide insight into the condition of women farmers, especially those who have headed households, so they can pay attention to designing future rural development policies.